2011
DOI: 10.1007/s10494-011-9327-2
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of the Sensitivity of Vortex Breakdown and Flame Stabilisation to Axial Forcing

Abstract: The effect of axial forcing on the flame/vortex breakdown interaction is studied, with particular focus on the Precessing Vortex Core (PVC). Large Eddy Simulation (LES), together with a filtered flamelet model describing the subgrid combustion, is performed to study a lean premixed flame undergoing mass flow fluctuations in a wide range of frequencies and amplitude. In average, forcing at frequencies lower than the PVC characteristic frequency moves the recirculation zone upstream the combustor in the premixin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 52 publications
2
24
1
Order By: Relevance
“…Such simulations correctly retrieve velocity profiles and PVC in cold and reactive conditions of swirl stabilized flames (Roux et al 2005, Freitag & Janicka 2007. Numerical results may in turn be used to determine the swirl number and analyze PVC interactions with the flame (Iudiciani & Duwig 2011), a problem that requires advanced optical diagnostics in experiments. Palies et al (2011e) used LES to infer the coupling mechanisms between large-scale vortices and swirl number oscillations leading to heat-release rate interferences.…”
Section: Large Eddy Simulation In Swirling Flame Dynamicsmentioning
confidence: 99%
“…Such simulations correctly retrieve velocity profiles and PVC in cold and reactive conditions of swirl stabilized flames (Roux et al 2005, Freitag & Janicka 2007. Numerical results may in turn be used to determine the swirl number and analyze PVC interactions with the flame (Iudiciani & Duwig 2011), a problem that requires advanced optical diagnostics in experiments. Palies et al (2011e) used LES to infer the coupling mechanisms between large-scale vortices and swirl number oscillations leading to heat-release rate interferences.…”
Section: Large Eddy Simulation In Swirling Flame Dynamicsmentioning
confidence: 99%
“…The reason for the frequency selection was to promote the formation of large-scale ring-like vortices beyond the nozzle rim due to strong oscillations of bulk velocity. According to Iudiciani and Duwig (2011), the frequency of the forcing can have a rather wide range of values that are smaller than the precession frequency. St ¼ 0.55 was also close to the value of 0.52, which was used for previous measurements by Alekseenko et al (2008) for a nonreacting jet with the same nozzle geometry.…”
Section: Experimental Setup and Apparatusmentioning
confidence: 99%
“…Strong perturbations were applied to the flow bulk velocity in order to force formation of ring-like vortices before the combustion domain and to investigate the effect on the combustion process. For example, based on large eddy simulation of a lean swirling flame in a model combustor, Iudiciani and Duwig (2011) have shown that application of periodic forcing with frequencies below the precession frequency of the vortex core can result in a weakening of the core precession and, consequently, shift RZ and the flame upstream of the combustor.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, they are often limited to the analysis of the system response to a single forcing frequency or to the simulation of the dynamics of self-sustained oscillations initiated from small or finite-level initial perturbations to a limit cycle. [21][22][23] System identification tools have also been applied to LES simulations to estimate the flame transfer function. 24,25 These techniques are based on the forcing of the flame using a small-amplitude broadband noise, assuming the flame response to be linear.…”
Section: Introductionmentioning
confidence: 99%